A QUANTITATIVE ETHNOBOTANICAL STUDY OF COMMON HERBAL REMEDIES USED AGAINST 13 HUMAN AILMENTS CATERGORIES IN MAURITIUS - Mahomoodally, Fawzi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background and aim: Mauritius is a tropical multicultural island with a long-standing use of herbal remedies. The present ethnobotanical survey was geared towards documenting and preserving local knowledge pertaining to common medicinal plants (MP) used as therapeutic agents in Mauritius. Methods: Interviews were conducted among local people and herbalists (n=318). Also, 7 quantitative ethnobotanical parameters (variety of use (VU), relative frequency of citation (RFC), informant consensus factor (FIC), fidelity level (FL), index of agreement on remedies (IAR), relative importance (RI) and cultural importance index (CII)) were calculated for MP used. Results: A total of 87 plants belonging to 45 families were reported to be used in formulating herbal remedies among which 3 endemic plants have been documented. Mentha piperita was found to be the most used plant against gastrointestinal diseases with an RFC index of 0.55. Holy basil (Ocimum tenuiflorum) had the highest RI value (RI=2.00), being cited for 9 different ailments. Therapeutic properties of some herbal remedies reported correlated to some extent with those of previous studies while others have open potential perspectives for further research as their chemistry and pharmacology have not been published. Conclusion: From the information obtained, it can be suggested that the Mauritian population still relies heavily on MP for their primary health care. Nonetheless, further research is needed to investigate the possible active constituents that could be the basis of an evidence based investigation to discover new drugs.